If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 = -22 + d Solving -39 = -22 + d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. -39 + -1d = -22 + d + -1d Combine like terms: d + -1d = 0 -39 + -1d = -22 + 0 -39 + -1d = -22 Add '39' to each side of the equation. -39 + 39 + -1d = -22 + 39 Combine like terms: -39 + 39 = 0 0 + -1d = -22 + 39 -1d = -22 + 39 Combine like terms: -22 + 39 = 17 -1d = 17 Divide each side by '-1'. d = -17 Simplifying d = -17
| 4a^2+b^2+12a-4b+13=0 | | 6x^2-23=-21 | | 4+7x=-32+x | | 35=7/3w | | -36+8b=4(3+4b) | | a+23=25 | | (5x)+7=-2x | | 2c-10+6= | | -58x-2+6=8x-230.6 | | 262.818/28.26 | | x(2x-2)+x(2x-4)=(4x+7)(x-3) | | (2x^4+7x^3-8)-(7x^2-5x+4)= | | -2-5x=-2(1+4x) | | 1/2*b*19.8 | | 7g+8=22 | | 0.2x=-0.7 | | R=1-2n+5 | | 4x+4x+3=0 | | 14-12=x/-4 | | 5x/4-3=7x/6 | | 17-3(4-3x)=6x-1 | | (-2z/y^3)^2 | | 1/3(m-3n)=2 | | 3x(-5)/2x | | 0.55=logx | | -4-p=8p-5(6+7p) | | (3xy^2-2y)=0 | | f(2e^4)=lnx | | 2=4-2f | | 81/54 | | 10x-20=-5x+10 | | -15=-k-4k |